Role of the non‐hypervariable FR3 D‐E loop in single‐domain antibody recognition of haptens and carbohydrates. Issue 11 (18th August 2019) - Henry, Kevin A.; Hussack, Greg; Kumaran, Jyothi; Gilbert, Michel; MacKenzie, C. Roger; Sulea, Traian; Arbabi‐Ghahroudi, Mehdi
Abstract: Single‐domain antibodies (sdAbs), the variable domains of camelid heavy chain‐only antibodies, are generally thought to poorly recognize nonproteinaceous small molecules and carbohydrates in comparison with conventional antibodies. However, the structures of anti‐methotrexate, anti‐triclocarban and anti‐cortisol sdAbs revealed unexpected contributions of the non‐hypervariable "CDR4" loop, formed between β‐strands D and E of framework region 3, in binding. Here, we investigated the potential role of CDR4 in sdAb binding to a hapten, 15‐acetyl‐deoxynivalenol (15‐AcDON), and to carbohydrates. We constructed and panned a phage‐displayed library in which CDR4 of the 15‐AcDON‐specific sdAb, NAT‐267, was extended and randomized. From this library, we identified one sdAb, MA‐232, bearing a 14‐residue insertion in CDR4 and showing improved binding to 15‐AcDON by ELISA and surface plasmon resonance. On the basis of these results, we constructed a second set of phage‐displayed libraries in which the CDR4 and other regions of three hapten‐ or carbohydrate‐binding sdAbs were diversified. With the goal of identifying sdAbs with novel glycan‐binding specificities, we panned the library against four tumor‐associated carbohydrate antigens but were unable to enrich binding phages. Thus, we conclude that while CDR4 may play a role in binding of some rare hapten‐specific sdAbs, diversifying this region through molecular engineering is probably not a general solution to sdAb carbohydrate recognition in the absence of a paired VL domain. Abstract : Three‐dimensional structural models of the anti‐15‐acetyl‐deoxynivalenol sdAb NAT‐267 (left) and its CDR4‐engineered derivative, MA‐232 (right), bearing a 14‐residue insertion in the FR3 D‐E loop. CDR4 is colored in blue with side chains shown. CDR1, CDR2, and CDR3 are colored in red, and the rest of the sdAb is shown in gray. Extension of the NAT‐267 CDR4 loop resulted in higher‐affinity binding to 15‐acetyldeoxynivalenol. However, CDR4‐randomized sdAb libraries failed to yield novel glycan‐specific sdAbs.